2012
DOI: 10.1530/eje-12-0060
|View full text |Cite
|
Sign up to set email alerts
|

Circulating progranulin levels in women with gestational diabetes mellitus and healthy controls during and after pregnancy

Abstract: Objective: Progranulin (PGRN) was recently introduced as a novel marker of chronic inflammatory response in obesity and type 2 diabetes capable of directly affecting the insulin signaling pathway. This study aimed to investigate the role of PGRN in gestational diabetes mellitus (GDM), which is regarded as a model for early type 2 diabetes. Methods: PGRN serum levels were measured in 90 pregnant women (45 GDM and 45 normal glucose tolerance (NGT)). In addition, PGRN was measured during a 2-h, 75 g oral glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(31 reference statements)
0
12
1
Order By: Relevance
“…Given that some patients had converted to MCI or DAT at the time of sample collection, we studied whether diagnosis, PiB uptake scores, or APOE genotypes were associated with PGRN levels. For example, it is known that PGRN levels are elevated due to inflammation or other clinical conditions such as pregnancy or cancer 21,22 ; however, whether these conditions similarly affect plasma and CSF PGRN levels is unknown. Determining PGRN levels in patients with DAT was not the primary objective of this study and the number of affected subjects that we analyzed was low; however, these findings are consistent with previous studies reporting no significant difference in plasma PGRN levels in patients with Alzheimer disease (AD) as compared with controls.…”
Section: Resultsmentioning
confidence: 99%
“…Given that some patients had converted to MCI or DAT at the time of sample collection, we studied whether diagnosis, PiB uptake scores, or APOE genotypes were associated with PGRN levels. For example, it is known that PGRN levels are elevated due to inflammation or other clinical conditions such as pregnancy or cancer 21,22 ; however, whether these conditions similarly affect plasma and CSF PGRN levels is unknown. Determining PGRN levels in patients with DAT was not the primary objective of this study and the number of affected subjects that we analyzed was low; however, these findings are consistent with previous studies reporting no significant difference in plasma PGRN levels in patients with Alzheimer disease (AD) as compared with controls.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating progranulin levels are higher in insulin-resistant, compared with insulin-sensitive, obese individuals [58] , and, most recently, increased plasma progranulin levels were reported in individuals with T2D, as well as in obese individuals [2] . Other recent studies reported that circulating progranulin levels are independent of BMI and/or insulin, but these studies included subjects with complicating conditions, such as gestational diabetes [59] , renal failure [60] , or post-nutritional weight loss [61] . Thus, in the absence of specific comorbid conditions, circulating progranulin levels appear to be a useful biomarker for inflammation and T2D related to obesity.…”
Section: Progranulin Is Linked To Metabolic Diseases Including Type mentioning
confidence: 99%
“…Elevated serum PGRN levels have also been reported in autoimmune disorders such as systemic lupus erythematosus and certain infectious conditions (Tanaka et al, 2012). Serum PGRN levels are also markedly elevated in mothers during gestation and show strong positive correlation with estrogen and progesterone (Todoric et al, 2012). …”
Section: Part 1: Pgrn Expressionmentioning
confidence: 99%